Occidentalist Perceptions of European Architecture in Nineteenth-Century Persian Travel Diaries Travels in Farangi Space - Vahdat, Vahid (Taylor & Francis, 2017)
In the midst of Europe's nineteenth-century industrial revolution, four men embarked on separate journeys to the wondrous Farangestan - a land of fascinating objects, mysterious technologies, heavenly women, and magical spaces. Determined to learn the secret of Farangestan's advancements, the travelers kept detailed records of their observations. These diaries mapped an aspirational path to progress for curious Iranian audiences who were eager to change the course of history. Two hundred years later, Travels in Farangi Space unpacks these writings to reveal a challenging new interpretation of Iran's experience of modernity. This book opens the Persian travelers' long-forgotten suitcases, and analyzes the descriptions contained within to gain insight into Occidentalist perspectives on modern Europe. By carefully tracing the physical and mental journeys of these travelers, the book paints a picture of European architecture that is nothing like what one would expect.